2021
DOI: 10.1002/adem.202100365
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and Investigation of In Situ and Ex Situ Produced Aluminum Matrix Foam‐Filled Tubes

Abstract: Composite metal foams (CMFs) are hybrid structures, which are usually produced from separate parts, and not in one step as functional, structural elements. Functional CMFs are characterized by high strength, high stiffness, and extreme energy absorbing properties compared with conventional metallic foams, which allow them to be used as load‐bearing and energy absorbing elements. Test specimens are made in AlMgSi0.5 tubes with the wall thickness of 5 mm. AlSi12 casting alloy is used as matrix material. To ensur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…During each type of measurement, the CFFHS structures significantly had higher strength and energy absorption than CMFs, especially during the bend tests, making lightweight CMF core structures applicable as components with not purely axial Figure 10. Specific energy absorption of various FFHSs under axial compression at ambient temperature, obtained from research articles, [7,8,[10][11][12][13][14]16,20,21,[24][25][26][27][28][29][30][35][36][37][38][39][40] compared to the CFFHSs developed in this research. Note: the specific energy absorption was calculated up to 0.5 strain if not shown otherwise on the diagram.…”
Section: Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…During each type of measurement, the CFFHS structures significantly had higher strength and energy absorption than CMFs, especially during the bend tests, making lightweight CMF core structures applicable as components with not purely axial Figure 10. Specific energy absorption of various FFHSs under axial compression at ambient temperature, obtained from research articles, [7,8,[10][11][12][13][14]16,20,21,[24][25][26][27][28][29][30][35][36][37][38][39][40] compared to the CFFHSs developed in this research. Note: the specific energy absorption was calculated up to 0.5 strain if not shown otherwise on the diagram.…”
Section: Comparisonmentioning
confidence: 99%
“…The fabrication of these structures can be defined based on the manufacturing steps as in situ or ex situ. In situ metal FFTs are produced in one step; [ 7–9 ] the foam manufacturing process takes place in the tube, while during the ex situ method, the metal foam is machined to an appropriate size after production and then placed or fixed into a tube.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that most of the systems discussed in the literature (Figure 13) were produced via the melt route. [43,50,63,64] Further, the addition of B 4 C particles could have increased the collapsible strength of the cells and delayed the cell wall collapse, leading to better energy absorption capacity. [57,65,66] However, it is difficult to make a one-to-one comparison due to the different foaming routes and processing parameters employed in various studies.…”
Section: Energy Absorption Of Various Foam Systemsmentioning
confidence: 99%
“…Orbulov et al showed that using EC nodules could reduce economic costs and potentially synthesize ASFs for the transport industry [ 23 ]. Subsequently, Kemeny et al and Leveles et al [ 24 , 25 , 26 ] demonstrated that using EC-ASF (AlSi12) as filler of an AlMgSi0.5 tube (ASF-FFT) improves the compressive performance. Furthermore, it was found that ex-situ filled tubes and bimodal ASF-FFT embedding EC in different sizes (2.5–3 and 3.5–4 mm) with the same volume ratio enhance the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%